Underwater repair technology - Nixon, John H. (Gulf Pub., 2000)
Annotation The book provides an comprehensive overview of the techniques available for the joining and repair of offshore structures. Nixon starts with joining systems that do not require welding and then explores the associated engineering systems needed for joining procedures. Topics include pipe handling, hyperbaric chamber design, and principal underwater welding techniques, including wet, one atmosphere, and hyperbaric. Nixon also includes a description of the effects of environmental pressure on the various hyperbaric welding processes. A complete guide to underwater welding, this book also discusses technologies that show promise in the laboratory, but are not currently in use. Nixon provides appendices describing the relevant diving technologies, basic oceanography, and the research methods used in the development of hyperbaric welding.
Keywords: Underwater welding and cutting.; Underwater construction -- Maintenance and repair.; elektronické knihy; electronic books